The present and future of withdrawal period calculations for milk in the European Union: focus on heterogeneous, nonmonotonic data. Issue 3 (7th September 2016) - Chevance, A.; Jacques, A.‐M.; Laurentie, M.; Sanders, P.; Henri, J.
Abstract : Harmonization of the method for calculating the withdrawal period for milk dates from the 1990s. European harmonization has led to guidance with three accepted methods for determining the withdrawal period for milk that are currently applicable. These three methods can be used by marketing authorization holders, but, in some cases, their diversity can lead to very different withdrawal periods. This is particularly the case when concentrations in milk are nonmonotonic and heterogeneous, meaning that concentrations strictly increase and then strictly decrease with significant interindividual variability in the time to reach the maximal concentration. Here, we first describe the concepts associated with the different methods used in the harmonized approach currently applicable for the determination of milk withdrawal periods, and then, we propose the application of a modern pharmacometric tool. Finally, with a nonmonotonic heterogeneous dataset, we illustrate the usefulness of this tool in comparison with the three currently applicable methods and discuss the limitations and advantages of each method.